Comparison of Gut Microbiota Diversity and Predicted Functions Between Healthy and Diseased Captive Rana dybowskii - Tong, Qing; Cui, Li-Yong; Du, Xiao-Peng; Hu, Zong-Fu; Bie, Jia; Xiao, Jian-Hua; Wang, Hong-Bin; Zhang, Jian-Tao (Frontiers in Microbiology, 2020)
The gut microbiota plays a key role in host health, and disruptions to gut bacterial homeostasis can cause disease. However, the effect of disease on gut microbiota assembly remains unclear, and gut microbiota-based predictions of health status is a promising yet poorly established field. Using Illumina high-throughput sequencing technology, we compared the gut microbiota between healthy (HA and HB) and diarrhoeic (DS) Rana dybowskii groups and analysed the functional profiles through phylogenetic investigation of communities by reconstruction of unobserved states (PICRUSt) analysis. In addition, we estimated the correlation between gut microbiota structures and predicted the functional compositions. The results showed significant differences in the phylogenetic diversity (Pd), Shannon, and observed richness (Sobs) indices between the DS and HB groups, with significant differences observed in the gut microbiota composition between the DS group and the HA and HB groups. Linear discriminant analysis (LDA) effect size (LEfSe) results revealed that Proteobacteria were significantly enriched in the DS group; Bacteroidetes were significantly enriched in the HA and HB groups; and Aeromonas, Citrobacter, Enterococcus, Hafnia-Obesumbacterium, Morganella, Lactococcus, Morganella, Providencia, Vagococcus, and Staphylococcus were significantly enriched in the DS group. Venn diagrams revealed that there were many more unique genera in the DS group than in the HA and HB groups. One hundred two sensitive species were selected using the indicator method, of which 33 indicated a healthy status and 69 (e.g., Acinetobacter, Aeromonas, Legionella, Morganella, Proteus, Providencia, Staphylococcus, and Vagococcus) indicated a diseased status. There was a significant and positive association between the composition and functional composition of the gut microbiota, indicating low functional redundancy of the frog gut bacterial community. Rana dybowskii disease was associated with changes in the gut microbiota, which subsequently disrupted bacterial-mediated functions. The results of this study can aid in revealing the effect of the R. dybowskii gut microbiota on host health and provide a basis for elucidating the mechanism of the occurrence of R. dybowskii disease.